2015
DOI: 10.2146/ajhp140388
|View full text |Cite
|
Sign up to set email alerts
|

Decision support at the point of prescribing to increase formulary adherence

Abstract: The incorporation of hard-stop CDS alerts into the CPOE system improved the overall rate of prescriber adherence to institutional therapeutic interchange protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 16 publications
0
29
0
Order By: Relevance
“…Similar to prior studies, ours was not a randomized control trial [ 17 23 ]. We also had access only to prescription claims data and could not control for important patient-level characteristics such as age, gender, and co-morbidities which can impact drug costs and adherence [ 31 ].…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Similar to prior studies, ours was not a randomized control trial [ 17 23 ]. We also had access only to prescription claims data and could not control for important patient-level characteristics such as age, gender, and co-morbidities which can impact drug costs and adherence [ 31 ].…”
Section: Discussionmentioning
confidence: 67%
“…Also, changes in out-of-pocket costs were similar, meaning the total drug cost savings did not come from choosing formulary versus non-formulary drugs, or from choosing lower tiered drugs which would have led to lower out-of-pocket costs. This is surprising since prior studies show that giving formulary and drug cost information to providers increases their prescribing of generic and formulary preferred drugs [ 17 23 ]. In our study, the lower increase in yearly total drug costs were in part due to the study group experiencing slower increases in total drug costs per 30-day supply for their brand-name and generic drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For 16 of these, the definition was similar: hard-stop alerts are automatic warning messages meant to communicate essential information to the clinician using an EHR that either prevent the user from taking an action altogether or allow the user to proceed only with the external override of a third party. 7,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] For 3 of the remaining studies, the definition was most consistent with what we have termed a soft stop-an automatic warning message meant to provide information that may change the clinician's course of action but can be ignored or overridden with only minimal action (such as clicking an acknowledgement reason). [24][25][26] In the final 2 studies, the term "hard stop" was used but not defined.…”
Section: Data Sources and Searchesmentioning
confidence: 99%
“…Therapeutic interchange policies exist in most hospitals (87%) [20]. A recent study showed prescribing adherence improved with alerts displayed for intranasal steroid, nonbarbiturate sedatives, and hypnotics during the inpatient ordering process [21]. Evidence suggests that to date, cost-saving measures such as therapeutic interchange have not been effective in outpatient settings [22].…”
Section: Introductionmentioning
confidence: 99%